Progress and prospects of urban and rural construction land reduction research in China - ZHAO Xiaofeng, TU Liuxin, MENG Hao, JIANG Qinchao, FU Shu (Ziyuan Kexue, 2024)
[Objective] The reduction of urban and rural construction land is an important proposition with the tendency of population decline in the latter stages of urbanization. Our research provided reference for optimizing the allocation of urban and rural construction land and promoting the governance of national territory. [Methods] This study examined the connotation, spatiotemporal evolution, driving mechanism, and approaches of urban and rural construction land reduction in China through literature review, and proposed the directions and major tasks for future research. [Results] The connotation of urban and rural construction land reduction has shifted from scale control to improvement of quality, efficiency and layout. The spatiotemporal evolution of urban and rural construction land reduction mainly focused on the estimation of reduction potential and its spatial differentiation. Urban shrinkage and rural hollowing out brought by population loss and industrial recession have reduced the urban and rural construction land. Approaches to urban and rural construction land reduction include redevelopment of inefficient land, linkage between increase and decrease of urban and rural construction land, linkage between increase and storage of construction land and comprehensive land remediation of the entire region. [Conclusion] Future research should focus on the main stream of “theoretical cognition - spatiotemporal evolution - regulation model - effects of reduction”, directed by the regional system theory of human-environment relationship. Research on the connotation, evolution and spatial difference of urban and rural construction land reduction in different regions and at different spatial scales should be strengthened. Case studies and summary of models should be emphasized to enhance the multiple effect analyses and comparative studies.